The innate interfacial elastic strain field of a transformable B2 precipitate embedded in an amorphous matrix - Fu, Xiaoling (2024)
When a transformable B2 precipitate is embedded in an amorphous matrix, it is often experimentally observed that the crystalline-amorphous interface not only serves as an initiation site for the martensitic transformation due to local stress concentrations, but also as an inhibitor to stabilize the transformation, the latter being attributed to the “confinement effect” exerted by the amorphous matrix, according to the Eshelby solution. These two seemingly incongruous factors are examined in this study using molecular dynamics simulations from an atomic interaction perspective. An innate strain gradient in the vicinity of the crystalline-amorphous interface is identified. The actual interface, the compressive/dilatative transition, and the interfacial maximum strain are investigated to differentiate from the conventional “interface” located within a distance of a few nanometers. Our innate interfacial elastic strain field model is applicable for the design of materials with a higher degree of martensitic transformation and controllable stress concentration, even in cryogenic environments.